Interactive effects of maize straw incorporation and improved irrigation on soil physicochemical properties and microbial community structure in saline–alkaline soil - Chai, Wenbo; Xu, Hanyuan; Yuan, Chao; Li, Shufen; Li, Hongtao; Zhu, Qing; Ji, Wei; Chi, Ming; Wang, Jun; Xin, Chongxing (Frontiers in Microbiology, 2026)
IntroductionSaline–alkali soils severely limit agricultural Q7 productivity and ecological sustainability, particularly in coastal regions.This study evaluated the interactive effects of maize straw incorporation and improved irrigation on soil physicochemical properties, enzyme activities, and microbial community structure in saline–alkali soil through a field experiment.MethodsSoil organic matter, nitrogen forms, available nutrients, salinity, and electrical conductivity were determined, together with key enzyme activities (sucrase and polyphenol oxidase) and bacterial and fungal community composition. Microbial functional potential was further explored using functional gene prediction.ResultsCompared with the control, the combined treatment significantly increased soil organic matter by 86.73% and available nutrients by 59.28%, while markedly reducing soil salinity and electrical conductivity by 53.56 and 47.12%, respectively. Soil enzyme activities responded differentially, with sucrase activity increasing by 109.23% and polyphenol oxidase activity decreasing by 29.35% compared with the control. Microbial community composition shifted substantially, characterized by a decline in halotolerant taxa (e.g., Flavobacteriaceae) and enrichment of carbon-cycling–associated bacteria (e.g., Cyanobiaceae), along with increased relative abundance of functional fungi such as Psathyrellaceae. Functional gene prediction revealed significant upregulation of carbohydrate metabolism pathways, including glycolysis and the tricarboxylic acid (TCA) cycle, indicating enhanced microbial metabolic capacity.DiscussionOverall, maize straw incorporation combined with improved irrigation effectively enhanced soil quality, reshaped microbial community structure, and strengthened microbial functional potential. These findings provide practical evidence that integrated straw–irrigation management can serve as a feasible and sustainable strategy for the remediation and productive utilization of saline–alkali soils.